A novel pattern language method for tradespace exploration: application to space mission architecting - Rüede, Anne-Marlene; Chavy-Macdonald, Marc-André; Rinalducci, Antonio; de la Osa, Nils Pachler; de Weck, Olivier; Huang, Jeffrey; Kneib, Jean-Paul (Journal of engineering design, 2025)
With the growing complexity of systems across diverse domains, key challenges emerge in simultaneously designing networks and their underlying infrastructure, requiring resolution at concept stage. In space mission design, technological advancements and ambitious goals enable numerous mission architecture concepts due to diverse material flow options. Current design support tools function either after the initial concept design, or tend to rapidly converge toward point solutions, limiting the solution space. We introduce a digital tool for early-stage concept design, capable of generating, evaluating, and visualising a wide range of user-defined architectural options. It utilises a pattern language for space missions, incorporating building blocks like 'launch' or 'electrolysis'. Validation with historic missions showcase the tool automatically identifies all four main mission architectures considered during the Apollo design and more, and accurately recommending the Lunar Orbit Rendezvous architecture which was actually selected. Predicted masses, informing costs, vary by 15% and duration by 30% from actual values, which is within expectations. Identifying missions and leveraging expert knowledge is also demonstrated in the Mars Sample Return case. This approach can help minimise the risk of overlooking effective mission concepts early on. Furthermore, the method is applicable in other domains facing concurrent infrastructure and logistics design challenges.